2020
DOI: 10.1080/2162402x.2020.1830524
|View full text |Cite
|
Sign up to set email alerts
|

Converging focal radiation and immunotherapy in a preclinical model of triple negative breast cancer: contribution of VISTA blockade

Abstract: Antibodies targeting the co-inhibitory receptor programmed cell death 1 (PDCD1, best known as PD-1) or its main ligand CD274 (best known as PD-L1) have shown some activity in patients with metastatic triple-negative breast cancer (TNBC), especially in a recent Phase III clinical trial combining PD-L1 blockade with taxane-based chemotherapy. Despite these encouraging findings, however, most patients with TNBC fail to derive significant benefits from PD-L1 blockade, calling for the identification of novel therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“… Cao et al 58 Samples of TNBC (n=254) Immune cells and tumor cells by IHC VISTA was expressed on immune cells in 87.8% (223/254) of the samples, and on tumor cells in 18.5% (47/254) of the samples. Pilones et al 59 4T1 murine mammary cancer model of metastatic and immune-resistant TNBC NA The efficacy of an antibody specific for VISTA was enhanced by focal RT. Cyclophosphamide + RT and dual PD-1/VISTA blockade had superior therapeutic effects, associated with activation of tumor-infiltrating CD8+ T cells and depletion of intratumoral granulocytic myeloid-derived suppressor cells.…”
Section: Vista Expression In Cancer and Its Value As An Immune Checkpoint: Preclinical Datamentioning
confidence: 99%
See 2 more Smart Citations
“… Cao et al 58 Samples of TNBC (n=254) Immune cells and tumor cells by IHC VISTA was expressed on immune cells in 87.8% (223/254) of the samples, and on tumor cells in 18.5% (47/254) of the samples. Pilones et al 59 4T1 murine mammary cancer model of metastatic and immune-resistant TNBC NA The efficacy of an antibody specific for VISTA was enhanced by focal RT. Cyclophosphamide + RT and dual PD-1/VISTA blockade had superior therapeutic effects, associated with activation of tumor-infiltrating CD8+ T cells and depletion of intratumoral granulocytic myeloid-derived suppressor cells.…”
Section: Vista Expression In Cancer and Its Value As An Immune Checkpoint: Preclinical Datamentioning
confidence: 99%
“… 58 A further step in the investigation of the therapeutic impact of VISTA in breast cancer was made by Pilones et al, who tested the combination of local radiotherapy and various immunotherapy strategies using a murine mammary cancer model of metastatic and immune-resistant TNBC. 59 They showed that the efficacy of an Ab specific for VISTA was enhanced by local radiotherapy, thus suggesting that a broad immunotherapeutic approach can help to increase durable responses in patients with TNBC. 59 …”
Section: Vista Expression In Cancer and Its Value As An Immune Checkpoint: Preclinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the combination of inhibitory ICs inhibitors with other cancer therapies might be another appealing strategy to increase the response rates of cancer therapies. Pilones et al have reported that focal radiotherapy and cyclophosphamide can increase the response rates to VISTA inhibitors and PD-1 inhibitors in mice bearing triple-negative breast cancers (84).…”
Section: Vista and Cancer Therapymentioning
confidence: 99%
“…Pilones et al. have reported that focal radiotherapy and cyclophosphamide can increase the response rates to VISTA inhibitors and PD-1 inhibitors in mice bearing triple-negative breast cancers ( 84 ).…”
Section: Vista and Cancer Therapymentioning
confidence: 99%